2020
DOI: 10.1101/2020.06.06.20122689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of COVID-19 control measures on social contacts and transmission in Kenyan informal settlements

Abstract: Background Many low- and middle-income countries have implemented control measures against coronavirus disease 2019 (COVID-19). However, it is not clear to what extent these measures explain the low numbers of recorded COVID-19 cases and deaths in Africa. One of the main aims of control measures is to reduce respiratory pathogen transmission through direct contact with others. In this study we collect contact data from residents of informal settlements around Nairobi, Kenya to assess if control measures have c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 19 publications
5
70
2
Order By: Relevance
“…Several studies have shown a very marked decrease in the number of contacts between the prepandemic and lockdown periods (9,(20)(21)(22)(23)(24), in agreement with what we found here, which parallels a decrease in mobility patterns (9,25). However, our study shows that the postlockdown increase in mobility patterns is not a good proxy of the daily number of in contacts in the four study locations (Supplementary Material, Sec.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown a very marked decrease in the number of contacts between the prepandemic and lockdown periods (9,(20)(21)(22)(23)(24), in agreement with what we found here, which parallels a decrease in mobility patterns (9,25). However, our study shows that the postlockdown increase in mobility patterns is not a good proxy of the daily number of in contacts in the four study locations (Supplementary Material, Sec.…”
Section: Discussionsupporting
confidence: 90%
“…[10][11][12][13] However, instituting these measures is also associated with deleterious economic and social, impacts, including large projected reductions in manufacturing, access to employment and basic necessities and educational advancement; and these effects appear to be greatest among those in lower-income and vulnerability categories. [14][15][16][17][18][19] Across the sub-Saharan African region, the Economic Commission for Africa projects an approximate 1.4% contraction in gross domestic product and that 25 million people are susceptible to entering extreme poverty. 20 Some have hypothesised that non-pharmaceutical interventions might be less effective in settings with large informal economies and limited ability to respond to increases in cases of severe disease, 21 and that their risks might outweigh their benefits.…”
Section: Open Accessmentioning
confidence: 99%
“…Frequently side-lined by the debates regarding the epidemiological data, public action against COVID-19 remains understudied today [2]. In early June, a rst study in Kenya with a sample of 213 people demonstrated the effectiveness of the policy package on the epidemic's reproductive rate [26]; however there is a lack of similar analysis in the Francophone West African region. The objective of this article is to describe and analyse the epidemiological evolution of COVID-19 in Francophone West Africa during the rst four months of the pandemic, as well as the public measures taken to deal with it.…”
Section: Introductionmentioning
confidence: 99%